CONTENT FEASIBILITY ANALYSIS OF GRADE X SENIOR HIGH SCHOOL PHYSICS BOOK - Lusiana Nursaputri; Zeni Haryanto; Muhammad Junus (Program Studi Pendidikan IPA FKIP Universitas Jember, 2021)
Textbooks play an essential role in students’ learning process. In physics learning, the textbooks could facilitate the scientific learning process. This study aims to find out the feasibility of the contents of the book entitled Physics Student Book 1 for Grade X Senior High School written by Purwanto Budi and Azam Muchammad 2019 published by PT Wangsa Jatra Lestari. Analysis of the feasibility of the contents of the book in this study is reviewed from several aspects, namely aspects of content feasibility, aspects of language, aspects of presentation, and aspects of graphic that BSNP has adjusted. The type of research used is qualitative descriptive research with check-list instrument as data collection tool. The analysis results in this study showed that in the aspect of content feasibility obtained a percentage of 80%, the linguistic aspect obtained a percentage of 78%, the presentation aspect obtained a percentage of 77%, and the aspect of graph obtained a percentage of 79%. These four aspects fall into the category of fulfilling, so the Physics Student Book 1 For Grade X Senior High School is worth to be used in the learning process.